К изучению фауны и экологии жуков семейств трубковертов (Attelabidae) и долгоносиков (Curculionidae), трофически связанных с тополями в условиях западных областей Украины - Лаврух, О.В. (Вестник зоологии, 1969)
Four species of beetles from the Attelabidae family and 19 ones from the Curculionidae family, trophically connected with the plants of the Populus genus, are known at the present time in the territory of the western regions of the Ukrainian SSR. The data on the ecology of the above-mentioned species are given in the article.